Prevalence of Diabetes Mellitus in Myocardial Infarction Patients -An Observational Study - Nikita Chauhan; Paras Chauhan (Journal of Biomedical and Pharmaceutical Research, 2023)
Abstract: Background: According to studies, having diabetes is a risk factor in and of itself for developing cardiovascular disease. The World Health Organization (WHO) reports that the worldwide burden of death and morbidity attributable to cardiovascular disease is increasing. Material & Methods: The present observational research was conducted at our tertiary care institution and lasted six months, from June to November 2022. We recruited 100 AMI patients upon receipt of written informed permission. Results: 60% of research participants had normal blood sugar levels, 25% previously knew they had diabetes mellitus, 11% had the diagnosis identified while they were hospitalized, and 4% experienced stress-related blood sugar elevations. Conclusion: In addition to being a predictor of prognosis and recurrences, elevated blood sugar was connected to acute cardiovascular problems, especially in those with acute myocardial infarction. Keywords: Risk factors, prevalence of diabetes mellitus, and acute myocardial infarction.